A Systematic Literature Review: Efektivitas Audit Kas dan Setara Kas dalam Meningkatkan Kualitas Laporan Keuangan - Miftahul Jannah; Muthia Muthia; Windi Elizha Putri; Erni Arniah; Nur Afifah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to examine the effectiveness of cash and cash equivalent audits in improving the quality of financial reports through a Systematic Literature Review (SLR) approach. The review process was conducted using the PRISMA flow, which includes identification, screening, feasibility assessment, and synthesis. Of the 60 articles identified in the 2020-2025 period, 26 articles met the inclusion criteria after a selection process based on duplication, relevance, and full-text accessibility. The analysis results indicate that cash and cash equivalent audits play a crucial role in strengthening the quality of financial reporting in various types of entities, including companies, non-profit organizations, village-owned enterprises (BUMDes), public-owned enterprises (BLUD), and financial institutions. Five key findings were consistent: increased cash balance accuracy, reduced risk of fraud and material misstatement, strengthened internal control, increased transparency and stakeholder trust, and improved overall financial report performance. Substantive audit procedures such as physical cash examinations, bank reconciliations, document verification, and verification proved effective in meeting audit assertions. Based on Agency Theory, effective cash audits can reduce information asymmetry, limit opportunistic management behavior, and strengthen accountability. This research provides theoretical contributions to the audit literature as well as practical applications for auditors, organizations, and regulators in strengthening internal control systems and conducting audit practices in the digital era.